Correlations among self-reported driving characteristics and simulated driving performance measures. (September 2014) - Stahl, Patrick; Donmez, Birsen; Jamieson, Greg A.
Following a driving simulator experiment investigating anticipatory competence in driving, participants were asked to rate themselves on driving characteristics that are potentially relevant to anticipatory competence. Significant correlations were found among multiple of these characteristics. Furthermore, all participants also completed the Manchester Driving Behaviour Questionnaire (DBQ), so that correlations between these subjective driving characteristics and DBQ categories could also be investigated. Findings showed that both subjective measures were generally aligned in that the DBQ categories correlated with the subjective characteristics describing them. However, no evidence could be found that participants judging themselves as safe drivers kept longer headways and larger times to collision, and no significant correlations were observed between subjective ratings of fuel-efficiency and fuel-consumption observed in the simulated drive. These findings suggest that caution should be taken when using self-reported driving characteristics to predict actual performance, and future research should further investigate the relation between self-reported measures and simulator performance measures.